2010
DOI: 10.1111/j.1464-410x.2010.09259.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and apoptosis by survivin small interfering RNA in bladder cancer cells

Abstract: OBJECTIVE To investigate the effects of survivin gene RNA interference on cell growth and the cell cycle in the human bladder cancer cell line T24. MATERIALS AND METHODS A small interfering RNA (siRNA) targeting survivin was transfected into T24 cells using a liposome approach. Reverse transcription‐polymerase chain reaction and Western blot analysis were used to examine survivin gene expression in T24 cells. Cells densities were determined by haematocytometer counts and flow cytometry was used for cell cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Survivin plays important roles in anti-apoptosis, so any method to decrease the expression of survivin in bladder cancer cells should elicit apoptosis (49,50). In this regard, survivin inhibitor YM155 promoted apoptosis of cancer cells (19,51), and we also observed that YM155 induced apoptosis in TCC cells with enhanced expression of cleaved PARP and phospho-histone γ-H2AX.…”
Section: Discussionmentioning
confidence: 51%
“…Survivin plays important roles in anti-apoptosis, so any method to decrease the expression of survivin in bladder cancer cells should elicit apoptosis (49,50). In this regard, survivin inhibitor YM155 promoted apoptosis of cancer cells (19,51), and we also observed that YM155 induced apoptosis in TCC cells with enhanced expression of cleaved PARP and phospho-histone γ-H2AX.…”
Section: Discussionmentioning
confidence: 51%
“…In addition to act as an apoptosis inhibitor, survivin is a key regulator of mitosis and is involved in G2/M transition. Besides, siRNA mediated down-regulation of survivin in bladder cancer cell lines, such as RT4 and T24, was associated with a specific G2/M arrest [47], [48]. Now, we showed that ciglitazone increased the fraction of RT4 and T24 (data not shown) cells in G2/M phase of the cell cycle.…”
Section: Discussionmentioning
confidence: 69%
“…In the case of RT4 cells, their cell cycle was not influenced by the treatment (Figure 10C), which can be explained by the cytoplasmatic localization of survivin in this cell line (Figure 10A). The decrease in viability observed previously (Figure 9), where RT4 cells showed the viability of 60% after anti-survivin siRNA-1 transfection could have been produced by the inhibition of cytoplasmic survivin, which induces apoptosis [21,43]. Previously, we studied the amount of survivin expressed by RT4 and T24 cells in a Western blot assay.…”
Section: Influence Of the Cell Cycle Arrest On Dual Therapy Efficacymentioning
confidence: 87%